Telework model using cloud computing technology / Muhammad Omar - Omar, Muhammad (2011)
The rapid development of information and communication technology (ICT) has become inevitable in our daily lives, especially in the management and technical fields. Introduction to a vast variety of the 'utilities computing' concept has been regarded as a strategic move to induce a healthy and balanced competitive growth. This particular technology is seen as a bright prospect in the economical management of year 2011, especially in the ICT sector. The introduction of cloud computing in Malaysia has enabled improvement in the operative management as well as significantly brings down the cost of operation in every organisation. Furthermore it has provided an ideal platform for the related organisations which implement the telework concept, which makes working away from the office a reality. The core purpose of this research is to identify organisations which implement the essential elements of telework and cloud computing, besides investigating factors which influence the telework to utilise cloud computing in management. This study is quantitative, whereby questionnaires were distributed to about 60 organisations under the Multimedia Super Corridor (MSC). The findings indicate that all factors identified of cloud computing have a positive relationship with telework. Next, this research developed a telework model using cloud computing, based on above factors; cost effectiveness, need for cloud computing, reliability, collaboration and security, as obtained from correlation statistics. The importance of this research could serve as guidance for other organisations to practice this particular technology and benefit individually, especially remained align with green ICT.